Nilai-Nilai Pendidikan Islam Dalam Tradisi Tahlilan Di Desa Batu Melenggang Kecamatan Hinai - Satria Wiguna; Ahmad Fuadi (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
In general, the tradition of praying for the dead is an activity carried out by reading the phrase